Qualitative and quantitative assessment of patient counseling occurring in a section of Gauteng's community pharmacies - Mukandabarasa, Monique Rwabuhungu (My University, 2008)
ABSTRACT This study intended to assess the nature and extent of patient counseling practice in a section of Gauteng’s community pharmacies and determine what factors have negative impact on the practice. Designed as a random cross-sectional survey, questionnaire-based engaging 60 pharmacists and 179 customers, it provided a “snapshot” of counseling services in the Johannesburg and Pretoria regions between January 2006 and September 2006. The outcomes measures assessed included the percentage of the actual practicing, the form of communication, number of items covered, and number of counseling steps accomplished. The findings showed about 74% of patients received at least one drug informational item as verbal advice, and an average of 62% of patients received six drug informational items of advice. Supplementary written information was given to 56% of patients some of the time when necessary or by request. The items of advice achieved at high rate were all about drug-instructions for use (>70%). Information about drug action, side effects and non-pharmacological advice occurred at low rate (<50). Significant difference (p<0.05) was observed between the two regions regarding the accomplishment of some items but no difference was noted referring to global counseling performance. Younger pharmacists overtook older pharmacists in performing some items (like telling when the medication begins to work: 53% versus 37%). Differences were also noted between pharmacists and other categories of dispensers with pharmacists proffering a higher level of quality and quantity of advice (e.g. counseling points summarized: 59% versus 30%). Workload, pharmacy type and gender were unrelated to current counseling practice. In conclusion, participating pharmacists showed good knowledge of the SA Gold Standard on counseling and satisfactory performed the counseling points. However, some expressed concern about the difficulty to accomplish some special GPP provisions. Future studies are advice to investigate the implementation of patient counseling from a nationwide sample of community pharmacies if the Professional Body regulating Pharmacy intends mandating counseling.
Keywords: patient counseling; community pharmacy